The Composer's Voice: "What women can do" - Dalen, Brenda (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1995)
In this interview, conducted on 18 August 1994, Violet Balestreri Archer revisits her past, recreating the experiences of her youth from the earliest days of her childhood in Como and Montreal to her graduation from Yale University in 1949 and sharing highly personal memories of her family, teachers, and friends. She recalls her first visit to Italy, her school years, her piano lessons, her early attempts at composition, her participation in the Montreal Women's Symphony, and her compositional studies with Douglas Clarke at McGill University, Béla Bartók in New York, and Paul Hindemith at Yale University. In listening to her story, we discover "who" she is and "how" she succeeded in establishing her compositional voice and in creating a space or "room" for herself in a profession traditionally dominated by men.